Is Green Manure from Riparian Buffer Strip Species an Effective Nutrient Source for Crops?. Issue 2 (1st March 2019) - Brown, Lawrie K.; Kazas, Charalampos; Stockan, Jenni; Hawes, Cathy; Stutter, Marc; Ryan, Casey M.; Squire, Geoffrey R.; George, Timothy S.
Abstract : Agriculture needs to reduce inputs of inorganic fertilizers and close the loop on nutrients that can otherwise become environmental pollutants. This can be achieved by promoting recycling of nutrients within the agricultural landscape. We investigated the extent to which plants found in riparian buffer zones have the potential to provide nutrients to crops as a green manure, through plant growth and decomposition studies. Under controlled conditions, species typical of Scottish riparian buffer strips were tested for their ability to accumulate biomass and nutrients in tissue under N‐ and P‐replete conditions and whether this ability enhanced the utility of the resulting green manure in promoting crop growth. In this proof‐of‐concept study, we found that green manure derived from riparian buffer strips did not effectively replace inorganic fertilizer and only had a significant positive effect on growth, yield, and nutrient accumulation in barley ( Hordeum vulgare L.) when it was integrated with the addition of inorganic fertilizers. The individual species tested varied in the amount of P they accumulated in their tissue (1.38–52.73 mg P plant −1 ), but individual species did not differ in their ability to promote yield when used as a green manure. Our results indicate that selecting certain species in the buffer strip on the basis of their nutrient accumulating abilities is not an effective way to increase the utility of buffer strip green manure as a nutrient source for crops. Core Ideas: We need to close the loop on nutrients that become environmental pollutants. Green manure from riparian buffer strips cannot replace chemical fertilizers. Buffer strip green manure integrated with fertilizer promotes plant growth. Common riparian buffer species have variation in nutrient accumulation. Selection of P‐ and N‐accumulating plants does not provide a superior green manure.